Tracing the linguistic crossroads between Malay and Tamil - Hoogervorst, Tom G. (UI Scholars Hub, 2015)
Speakers of Malay and Tamil have been in intermittent contact for roughly two millennia, yet extant academic work on the resultant processes of contact, lexical borrowing, and language mixing at the interface of these two speech communities has only exposed the tip of the proverbial iceberg. This paper presents an historical overview of language contact between Malay and Tamil through time and across the Bay of Bengal. It concludes with a call for future studies on the lexicology, dialectology, and use of colloquial language of both Malay and Tamil varieties.